ChemInform Abstract: Site‐Selective Multicomponent Synthesis of Densely Substituted 2‐Oxo Dihydropyrroles Catalyzed by Clean, Reusable, and Heterogeneous TiO2 Nanopowder. Issue 24 (23rd May 2013) - Rana, Sunil; Brown, Mike; Dutta, Arghya; Bhaumik, Asim; Mukhopadhyay, Chhanda
Abstract An environmentally benign process is developed for the reaction of diesters (I) or (IX) with aldehydes and 2 equiv.